2022
DOI: 10.1186/s40779-022-00383-2
|View full text |Cite
|
Sign up to set email alerts
|

Activated Drp1 regulates p62-mediated autophagic flux and aggravates inflammation in cerebral ischemia-reperfusion via the ROS-RIP1/RIP3-exosome axis

Abstract: Background Cerebral ischemia-reperfusion injury (CIRI) refers to a secondary brain injury that can occur when the blood supply to the ischemic brain tissue is restored. However, the mechanism underlying such injury remains elusive. Methods The 150 male C57 mice underwent middle cerebral artery occlusion (MCAO) for 1 h and reperfusion for 24 h, Among them, 50 MCAO mice were further treated with Mitochondrial division inhibitor 1 (Mdivi-1) and 50 MCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…However, these studies have primarily focused on inflammation and signaling cascade, and few have focused on the aberrantly expressed genes related to oxidative-damaged mitochondria and oxidative stress in AMI. Our study elucidated the process of vascular inflammation caused by myocardial ischemia from the perspective of mitochondrial quality imbalance and preliminarily explained the mechanism through the autophagic-exosome manner [ 23 ] in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have primarily focused on inflammation and signaling cascade, and few have focused on the aberrantly expressed genes related to oxidative-damaged mitochondria and oxidative stress in AMI. Our study elucidated the process of vascular inflammation caused by myocardial ischemia from the perspective of mitochondrial quality imbalance and preliminarily explained the mechanism through the autophagic-exosome manner [ 23 ] in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS fluorescence was excited by a 488 nm laser and emission was collected at 501–563 nm. Quantification for the ROS assay was conducted using ImageJ to measure the FITC fluorescence intensity [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The JC-1 aggregate fluorescence was excited by a 633 nm laser and emission was collected at 558-617 nm. Quantification for mitochondrial membrane potential was carried out to measure the fluorescence intensity ratio of JC-1 aggregate/JC-1 monomer [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research, the mitochondrial division inhibitor 1 (Mdivi-1) was extensively studied and found to reduce dynamin-related protein 1 (Drp1) levels and excessive mitochondrial fission, and can inhibit mitophagy through mitochondrial-targeting decreasing PINK1, PARK2 and LC3II levels, both in vivo and in vitro [ 11 , 13 , 14 , 15 ]. In order to clarify the effect of mitophagy on the radioresistance of A549R cells, Mdivi-1 was used in this study.…”
Section: Resultsmentioning
confidence: 99%